Nanopore Sequencing and De Novo Assembly of a Black-Shelled Pacific Oyster (Crassostrea gigas) Genome - Wang, Xiaotong; Xu, Wenjie; Wei, Lei; Zhu, Chenglong; He, Cheng; Song, Hongce; Cai, Zhongqiang; Yu, Wenchao; Jiang, Qiuyun; Li, Lingling; Wang, Kun; Feng, Chenguang (Frontiers in Genetics, 2019)
The Pacific oyster, Crassostrea gigas, belongs to one of the most species-rich phyla and provides important ecological and economical services. Here we present a genome assembly for a variety of this species, black-shelled Pacific oyster, using a combination of 61.8 Gb Nanopore long reads and 105.6 Gb raw BGI-seq short reads. The genome assembly comprised 3,676 contigs, with a total length of 587 Mb and a contig N50 of 581 kb. Annotation of the genome assembly identified 283 Mb (48.32 %) of repetitive sequences and a total of 26,811 protein-coding genes. A long-term transposable element active, accompanied by recent expansion (1 million years ago), was detected in this genome. The divergence time between black-shelled and the previous published Pacific oyster genome was estimated at about 2.2 million years ago, which implied that species C. gigas had great intraspecific genetic variations. Moreover, we identified 148/188 specifically expanded/contracted gene families in this genome. We believe this genome assembly will be a valuable resource for understanding the genetic breeding, conservation, and evolution of oysters and bivalve.